Diagnosis of cancer, autoimmune and infectious diseases and prediction of the therapy effectiveness based on the individual’s immunotype - Tabakov, Dmitry V.; Maznina, Anna A.; Astakhova, Ekaterina A.; Egorova, Anastasia E.; Zakharova, Elena N.; Glushkova, Olga V.; Petriaikina, Ekaterina S.; Svetlichnyy, Dmitry V.; Krupinova, Julia A.; Bogdanov, Viktor P.; Yudin, Vladimir S.; Keskinov, Anton A.; et al. (Frontiers in Immunology, 2025)
Immune system plays a central role in the pathogenesis of cancer and autoimmune diseases. An entire field has emerged to identify separate minor cell subpopulations carrying potential molecular targets or activation markers to study their prognostic role in disease progression and severity or predictive potential to use immunotherapy. However, the biomarker potential of minor populations is limited, as it does not take into account systemic interactions between populations of the immune system. A number of studies in the COVID era have shown that the certain balance between immune cell populations in donor’s blood, called ‘immunotype’, can predict the outcome of treatment and the onset of a cytokine storm. This observation was extended to other diseases, including cancer and autoimmunity. It was shown that the immunotype can be used to diagnose both the presence of the disease itself, as well as its form or progression, to stratify patients in the risk groups and to predict the effectiveness of therapy. The most important advantages of immunotype-based diagnostics are its low invasiveness, the possibility of multiple biomaterial sampling, and the complexity of the analysis by the simultaneous assessment of blood cell composition and their functional activity. In this review, we summarize currently available studies of immunotypes and defined key subpopulations, their possible impact in diagnostics and personalization of the therapy in clinical routine practice in various diseases.